I am a camera - Van Druten, John 1901-1957; Isherwood, Christopher 1904-1986; Arnold, Malcolm 1921-2006 (Studiocanal Limited, 2022)
"In Weimar-era Berlin, an aspiring writer strikes up a friendship with a vivacious, penniless singer." [imdb-com]
Original: Großbritannien 1955
Special features: Peter Parker on Christopher Isherwood ; interview with journalist and film critic Anna Smith ; stills gallery ; trailer
Bildformat 1.33:1
Keywords: Film; DVD-Video